Enabling Lambertian-Like Warm White Organic Light-Emitting Diodes with a Yellow Phosphor Embedded Flexible Film - Cheng-Chang Chen; Huang-Yu Lin; Cheng-Hung Li; Jin-Han Wu; Zong-Yi Tu; Li-Ling Lee; Ming-Shan Jeng; Chien-Chung Lin; Jwo-Huei Jou; Hao-Chung Kuo (International Journal of Photoenergy)
We demonstrate in this report a new constructive method of fabricating white organic light-emitting devices (OLEDs) with a flexible plastic film embedded with yellow phosphor. The flexible film is composed of polydimethylsiloxane (PDMS) and fabricated by using spin coating followed by peeling technology. From the results, the resultant electroluminescent spectrum shows the white OLED to have chromatic coordinates of 0.38 and 0.54 and correlated color temperature of 4200 K. The warm white OLED exhibits the yield of 10.3 cd/A and the luminous power efficiency of 5.4 lm/W at a luminance of 1000 cd/m2. A desirable Lambertian-like far-field pattern is detected from the white OLEDs with the yellow phosphor containing PDMS film. This method is simple, reproducible, and cost-effective, proving to be a highly feasible approach to realize white OLED.